2020
DOI: 10.1093/cercor/bhaa031
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Neurogenic Potential in the Ventricular–Subventricular Zone of Common Marmoset during Postnatal Brain Development

Abstract: Even after birth, neuronal production continues in the ventricular–subventricular zone (V–SVZ) and hippocampus in many mammals. The immature new neurons (“neuroblasts”) migrate and then mature at their final destination. In humans, neuroblast production and migration toward the neocortex and the olfactory bulb (OB) occur actively only for a few months after birth and then sharply decline with age. However, the precise spatiotemporal profiles and fates of postnatally born neurons remain unclear due to methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
(118 reference statements)
0
12
1
Order By: Relevance
“…In contrast to studies in ferrets, monkeys, and humans that reported a distinct decline of DCX expression, we found that the number of DCX + clusters remained constant from birth through toddlerhood in the piglet SVZ (Fig. 2) (Akter et al, 2020;Ellis et al, 2019;Paredes et al, 2016a;Sanai et al, 2011). These observations are in sharp contrast to previous findings in the piglet where DCX + cells decline with age (birth to 15 wks) and human studies were migrating immature neurons (DCX + cells) decline by 6 to 18 months of age (Morton et al, 2017;Paredes et al, 2016a;Sanai et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to studies in ferrets, monkeys, and humans that reported a distinct decline of DCX expression, we found that the number of DCX + clusters remained constant from birth through toddlerhood in the piglet SVZ (Fig. 2) (Akter et al, 2020;Ellis et al, 2019;Paredes et al, 2016a;Sanai et al, 2011). These observations are in sharp contrast to previous findings in the piglet where DCX + cells decline with age (birth to 15 wks) and human studies were migrating immature neurons (DCX + cells) decline by 6 to 18 months of age (Morton et al, 2017;Paredes et al, 2016a;Sanai et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…In humans, newborn neurons may take many months to mature and might maintain immature markers, such as DCX and/or PSA-NCAM, for a long time. In support of this, studies performed in sheep (Lévy et al, 2017;Piumatti et al, 2018), marmoset (Sawamoto et al, 2011;Akter et al, 2020), and macaques (Kohler et al, 2011) show that there are species differences in the maturation rate of neurons. Neurons can take up to 3 months to mature in the marmoset, compared with 3-4 weeks for mouse neurons (Petreanu and Alvarez-Buylla, 2002;Carleton et al, 2003;Zhao et al, 2006).…”
Section: Labels More Than Just Newborn Neuronsmentioning
confidence: 85%
“…Common marmosets are currently used as a model primate in the neuroscience field [24,25]. The aforementioned results suggest that GAP-43 in primates is phosphorylated at pT181 (T181 in primates corresponds to T172 in rodents) in their developing brains.…”
Section: Gap-43 In Developing Marmoset Brain Is Recognized By Pt172abmentioning
confidence: 98%
“…P1 marmoset brains were fixed and immunostained as described previously [62]. We used common marmosets to which 5-ethynyl-2′-deoxyuridine (EdU) was administered for the purpose of labeling proliferating cells as previously described [24]. Marmosets were deeply anesthetized with isoflurane and transcardially perfused with PBS followed by PFA in 0.1 M PB.…”
Section: Immunohistochemistry Using Ferret and Marmoset Brainsmentioning
confidence: 99%